2014
DOI: 10.1126/scitranslmed.3009835
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic bispecific antibodies cross the blood-brain barrier in nonhuman primates

Abstract: Using therapeutic antibodies that need to cross the blood-brain barrier (BBB) to treat neurological disease is a difficult challenge. We have shown that bispecific antibodies with optimized binding to the transferrin receptor (TfR) that target β-secretase (BACE1) can cross the BBB and reduce brain amyloid-β (Aβ) in mice. Can TfR enhance antibody uptake in the primate brain? We describe two humanized TfR/BACE1 bispecific antibody variants. Using a human TfR knock-in mouse, we observed that anti-TfR/BACE1 antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
282
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(305 citation statements)
references
References 16 publications
11
282
0
Order By: Relevance
“…A potential to deliver antibody therapeutics across the BBB, demonstrated recently with several BBB carrier antibodies, including TfR antibodies [5][6][7] and FC5, 11,13 has generated a renewed debate on mechanisms of internalization, intracellular traffic and polarized abluminal release of antibodies developed to cross the BBB via RMT. This study tracked the endocytic sorting and transcytosis of various internalizing and BBB-crossing antibody formats in BEC using a novel, quantitative mass spectrometry approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential to deliver antibody therapeutics across the BBB, demonstrated recently with several BBB carrier antibodies, including TfR antibodies [5][6][7] and FC5, 11,13 has generated a renewed debate on mechanisms of internalization, intracellular traffic and polarized abluminal release of antibodies developed to cross the BBB via RMT. This study tracked the endocytic sorting and transcytosis of various internalizing and BBB-crossing antibody formats in BEC using a novel, quantitative mass spectrometry approach.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, A20.1Fc showed slightly higher P app values in vitro and measurable CSF levels in vivo compared to A20.1, suggesting that Fc fragment may contribute to low, but detectable non-specific penetration of antibodies into the brain described in several studies. 5,6,13 A recent study 42 using high-resolution quantitative microscopy showed that lysosomal degradation of low levels of IgGs internalized into BEC from systemic circulations may be further limiting the antibody access to the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative scaffold-proteins are in general much smaller than full-length antibodies and can usually be engineered into multivalent as well as multispecific units with an overall size that remain smaller than the conventional antibody [17,18]. Such features can potentially improve in vivo biodistribution of the agent [19][20][21][22]. One type alternative binding-protein that has been investigated for various diagnostic and therapeutic applications is the small three-helical bundle Affibody molecule (6.5 kDa) [17,23].…”
mentioning
confidence: 99%
“…Inside the brain, the antibody releases the receptor, and, with the other arm, binds and disrupts its main target: the enzyme betasecretase, which produces the amyloid-beta protein that accumulates in the brain in Alzheimer's disease. In a proof-of-concept study in 2014, the team showed that intravenous injections of the antibody lowered amyloidbeta levels in the brains of monkeys (4).…”
Section: Trojan Horsesmentioning
confidence: 99%